Hayi%20Hak%2c%20Perdeye%20Yans%c4%b1yan%20Zaman%2c%20T%c3%bcrk%20G%c3%b6lge%20Tiyatrosu%20Karag%c3%b6z%c3%bcn%20K%c3%b6kenine%20Dair%20%c4%b0mgesel%20%c4%b0zler - Ökkeş Hakan Çetin; Burak Erhan Tarlakazan (History Studies International Journal of History, 2018)
Karagöz, qui est un jeu d'ombres turc, était une partie importante de la vie sociale avant les outils de communication comme le cinéma et le théâtre. Cependant, l'origine de ce jeu d'ombres a été étudiée par divers chercheurs, turcs et nationaux, et il y a encore une question sur son temps et son lieu. Les symboles visuels sont des outils de communication qui fournissent des informations sur les civilisations dans lesquelles ils sont créés, et fournissent une reconnaissance, une datation et une prise de conscience. En ce sens, les symboles, les œuvres et les images produits par la société turque ont le potentiel de donner des idées pour la source du jeu d'ombres turc. Certains symboles visuels qui sont produits avec différentes méthodes et techniques en

Karagöz, que es un juego de sombras turco, fue una parte importante de la vida social antes de las herramientas de comunicación como el cine y el teatro. Sin embargo, el origen de este juego de sombras ha sido investigado por varios investigadores, tanto turcos como nacionales, y todavía hay una pregunta sobre su tiempo y lugar. Los símbolos visuales son herramientas comunicativas que proporcionan información sobre las civilizaciones en las que se crean, y proporcionan reconocimiento, datación y conciencia. En este sentido, los símbolos, obras e imágenes producidas por la sociedad turca tienen el potencial de dar ideas sobre la fuente del juego de sombras turco. Algunos símbolos visuales que se producen con diferentes métodos y técnicas en

Karagöz, which is a Turkish shadowplay, was a significant part of the social life before communication tools like cinema and theater.However, origin of this shadowplay has been researched by various researchers, both Turkish and National, and there is still a question about its time and place.Visual symbols are communicative tools that provide information about the civilizations in which they are created, and provide recognition, dating and awareness.In this sense, the symbols, works and images produced by the Turkish society have the potential to give ideas for the source of the Turkish shadow theater.Some visual symbols which are produced with different methods and techniques in

Karagöz, which is a Turkish shadowplay, was a significant part of the social life before communication tools like cinema and theater.However, origin of this shadowplay has been researched by various researchers, both Turkish and National, and there is still a question about its time and place.Visual symbols are communicative tools that provide information about the civilizations in which they are created, and provide recognition, dating and awareness.In this sense, the symbols, works and images produced by the Turkish society have the potential to give ideas for the source of the Turkish shadowplay.Some visual symbols which are produced with different methods and techniques in

كان كاراغوز، وهو الظل التركي، جزءًا مهمًا من الحياة الاجتماعية قبل أدوات الاتصال مثل السينما والمسرح. ومع ذلك، فقد تم بحث أصل هذا الظل من قبل العديد من الباحثين، الأتراك والوطنيين، ولا يزال هناك سؤال حول زمانه ومكانه. الرموز المرئية هي أدوات تواصلية توفر معلومات حول الحضارات التي تم إنشاؤها فيها، وتوفر الاعتراف والتعارف والوعي. وبهذا المعنى، فإن الرموز والأعمال والصور التي ينتجها المجتمع التركي لديها القدرة على إعطاء أفكار لمصدر الظل التركي. بعض الرموز المرئية التي يتم إنتاجها بطرق وتقنيات مختلفة في
Keywords: Museology; Social Sciences; Digitizing and Virtualizing Folklore; Computer science; Arts and Humanities; Turkish Culture; 2. Zero hunger; 9. Industry and infrastructure; 4. Education; 16. Peace & justice; 3. Good health; 12. Responsible consumption; 11. Sustainability; 8. Economic growth; 10. No inequality